Report on Three Potential PPP Water Projects in the Ministry of Public Works - BPP SPAM - World Bank (Washington, DC, 2013)
The reaction by bilateral and multilateral agencies, the private sector and the Government of Indonesia to the Infrastructure Summit was an important step toward developing transactions that can assist infrastructure development throughout Indonesia. However, the commitments made by Government to these agencies and the private sector has not yet come to fruition. Many of the projects selected and advertised during the Summit required significant inputs to be attractive to private sector. In addition, certain key provisions required to ensure mature, well-defined and bankable transactions were often missing. A meeting between the Minister of Public Works and a World Bank delegation recently concluded that Water Supply projects are now in a position to be tendered with the expected issuance of water extraction licenses and a further examination of water supply have shown that some of the projects can proceed.The overall objective of the Review of Water Project Tender Documents is to ensure that from the list of projects noted above the most likely project is chosen for further analysis. This future analysis will include an update of previously prepared Tender Documents and a complete Request for Proposal that the private sector can bid on and lenders will find bankable. The current analysis will look closely at objective issues such as the demand for water within the relative municipalities, subjective issues such as concerns over raw water extraction licenses and local government security and at Sovereign issues that affect project bankability.